2017
DOI: 10.5325/transportationj.56.4.0357
|View full text |Cite
|
Sign up to set email alerts
|

Urban Logistics: Establishing Key Concepts and Building a Conceptual Framework for Future Research

Abstract: The world is rapidly urbanizing, causing businesses to rethink venerable principles related to logistics and distribution. As populations urbanize and customer service expectations escalate, firms seek new ways to serve urban customers but are often frustrated by numerous complexities inherent to the urban context. Through a systematic literature review, this research combines concepts and theories from multiple nonbusiness disciplines in order to provide a foundation for understanding the urban environments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 128 publications
0
51
0
3
Order By: Relevance
“…Logistics and transportation enable economic development, but they are traditionally quite inefficient in urban areas. As shown in Rose et al (2017), urban areas are characterized by the interplay of different stakeholder interest in close quarters, and, as highlighted in Kin et al (2017), megacities add growing sustainability challenges. Further obstacles include low load factors, empty trips, long dwell times at loading and unloading points, and large numbers of deliveries to individual customers (Cepolina and Farina, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Logistics and transportation enable economic development, but they are traditionally quite inefficient in urban areas. As shown in Rose et al (2017), urban areas are characterized by the interplay of different stakeholder interest in close quarters, and, as highlighted in Kin et al (2017), megacities add growing sustainability challenges. Further obstacles include low load factors, empty trips, long dwell times at loading and unloading points, and large numbers of deliveries to individual customers (Cepolina and Farina, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For the evaluation of SCL strategies, 6 evaluation criteria have been defined in accordance with a detailed literature review [5,9,12,14,15] and expert opinions:…”
Section: Defining Evaluation Criteriamentioning
confidence: 99%
“…Step 7: The negative ideal solutions of benefit-type and cost-type criteria for each alternative are calculated with Eq. (14). The result is provided in Table 7.…”
Section: The Prioritization Of Scl Strategiesmentioning
confidence: 99%
“…Additionally, some opportunities for research are identified: network design, omni-channels logistics, delivery systems, stakeholder cooperation, and sustainability. Finally, Rose et al [62] developed a systematic literature review, from different academic disciplines, highlighting the gaps regarding the defining features of urban logistics and proposing a framework of urban environmental factors affecting logistics operations. A remarkable contribution of this investigation is the definition of the concept of urban logistics in which an explicit mention to the existence of reverse flows occurring within urban systems is made.…”
Section: Urban Logisticsmentioning
confidence: 99%
“…A remarkable contribution of this investigation is the definition of the concept of urban logistics in which an explicit mention to the existence of reverse flows occurring within urban systems is made. This way, according to Rose et al [62], urban logistics is defined as "that part of supply chain management that plans, implements, and controls the efficient, effective forward and reverse flow and storage of goods, services, and related information between the point of origin and point of consumption in order to meet customers' requirements, as influenced by complex interactions among densely populated social systems and associated infrastructure".…”
Section: Urban Logisticsmentioning
confidence: 99%